2005
DOI: 10.1577/m03-230.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hatchery versus Wild Sockeye Salmon Fry Growth and Survival in Two British Columbia Lakes

Abstract: We evaluated the relative success of sockeye salmon hatchery fry stocking in two British Columbia-Alaska transboundary lakes (1,622-ha Tatsamenie Lake and 492-ha Tahltan Lake). Fry stocking began in the late 1980s and is still under way. During the study period, survival patterns in the two lakes were different. At Tatsamenie Lake, wild egg-to-fry survival was higher than hatchery egg-to-fry survival (11.3% versus 4.3%) and wild egg-to-smolt survival was higher than hatchery egg-to-smolt survival (5.8% versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…Hyatt et al. () reported wild Sockeye Salmon egg‐to‐smolt survival for Tatsamenie and Tahltan lakes in British Columbia as 5.8% and 3.6%, respectively. The SARs were also lower than those for northern populations in British Columbia and Alaska (range, 1.34% to 3.4%: Bradford ; range in Chilko Lake, British Columbia, 2% to 5%: DFO ) and upper Columbia River populations (range, 0.67% to 9.43%: Williams and Smith ; range, 0.2% to 23.5%: Williams et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hyatt et al. () reported wild Sockeye Salmon egg‐to‐smolt survival for Tatsamenie and Tahltan lakes in British Columbia as 5.8% and 3.6%, respectively. The SARs were also lower than those for northern populations in British Columbia and Alaska (range, 1.34% to 3.4%: Bradford ; range in Chilko Lake, British Columbia, 2% to 5%: DFO ) and upper Columbia River populations (range, 0.67% to 9.43%: Williams and Smith ; range, 0.2% to 23.5%: Williams et al.…”
Section: Discussionmentioning
confidence: 99%
“…We did not automatically include lower survival of stocked fish in the SCAA model because, as previously stated, there was no information available to suggest how survival might differ between stocked and wild fish or over what age-classes survival rates may be different. Further, some research has found stocked fish to have higher survival than wild fish (Hyatt et al 2005), so we did not feel comfortable simply making an assumption as to what survival rates were for stocked and wild fish.…”
Section: Discussionmentioning
confidence: 98%
“…It is entirely conceivable, perhaps even probable, that stocked Chinook salmon may have lower rates of survival than their wild counterparts, particularly during the first year of life. Several studies conducted on salmon species have indicated wild-produced fish have greater rates of survival early in life than stocked fish (Jonsson et al 2003;Saloniemi et al 2004;Hyatt et al 2005). If survival of stocked Chinook salmon is lower than that of wild fish in Lake Huron, than the estimates of wild reproduction of approximately 10 million fish may be extremely biased, and, as a consequence, our estimates of age-0 natural mortality rates are probably too large as well and partly function to reduce abundances to more appropriate levels.…”
Section: Discussionmentioning
confidence: 99%
“…Nickelson et al, 1986;Hyatt et al, 2005), and then compare hatchery programmes with other management tools. The latter should include spawning-bed enhancement (Merz et al, 2004), rehabilitation of channelized streams , and improvements to access for migratory fish (Sagawa et al, 2004), but fisheries management should be implemented more actively.…”
Section: Discussionmentioning
confidence: 99%